Collision Risk and Economic Benefit Analysis of Composite Separation for the Central East Pacific Track System. - Busch,Allen C; Colamosca,Brian; Vander Veer,John R (1977)
This report presents and evaluation of the application of composite separation to the Central East Pacific (CEP) track system. Criteria for the evaluation were a collision risk and an economic benefit's comparison of the existing four-route and proposed composite six-route systems. A 6-month data collection was performed. Radar data from land-based facilities in California and Hawaii and from Ocean Station Vessel November were processed to determine aircraft navigation performance. Utilization of the existing system was gauged from air traffic control facility data, and flight crew survey forms were used to collect information necessary for comparative analysis purposes. The report describes estimation of collision risk model parameters from the data. Lateral, longitudinal, and composite collision risk model risks were estimated for the existing and proposed composite systems based upon accepted North Atlantic Systems Planning Group (NAT/SPG) methodology, while vertical collision risk was calculated based upon previous NAT/SPG studies. Lateral collision risk for the proposed composite system was found to be lower than for the existing structure. Comparisons of fuel burn and flight times indicated that the proposite composite system would be more economically beneficial than the existing route configuration. As a result of the study, the proposed composite system was recommended for implementation on a trial basis. (Author)